LEGAL PROTECTION FOR OWNER DUAL LAND CERTIFICATES IN INDONESIA - Haspada , Deny (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2022)
Land is something Thing what 's inside is important life society . Land is something very valuable especially in the present where land the more little , so soil bes something of value quite expensive. Not a bit appear dispute land on land , for one is ownership certificate soil double . it becomes harmful owner the real original because the land anytime can sold by unauthorized owner . _ Owner legitimate can submit lawsuit as form protection provided inside _ _ law to defend right as owner legitimate from soil the .